Lumad ipagtanggol ang lupang ninuno - Regalado, Nonoy ([s.l.] Ibon Video Collection., 1994)
The Lumads of Mindanao, joined by various people's organizations and NGOs, unite to protect their lands from the incursions of multinational corporations.
VCD
Direction/Camera, Nonoy Regalado ; executive producers Marlene C. Francia, Roger Ricafort ; original script Arnold Molina Azurin ; translation in Filipino Ma. Jovita Zarate, Elena Cosio Cacanindin ; editing/sound Marlene C. francia ; Naration Jerry Peralta ; musical scoring Noy Regalado.
Maria Estonilo, Justin Nicolas, Ariel Saturay.
Keywords: Lumad--Mindanao--Philippines.